Una Mirada al Acto Pedagógico en Enseñanza de la Matemática en una Universidad Abierta-Venezuela - Rodríguez Cortez, Enedina Lady (2022)
Modeling the pedagogical act in a University of open and distance education, which allows the empirical execution of knowledge through the production by a content specialist, of an instructional module or master medium and the interaction mediated by an advisor to develop an adequate management, which needs to be implemented for the students' self-learning, is a complex process. By identifying several mismatches and formulating hypotheses about the adequacy of the study process, regarding its Epistemic facet, the study of the Didactic-Mathematical Knowledge of the Half-Master on the Affine Function applied to economics is approached, under the Didactic-Mathematical Knowledge Model of the Ontosemiotic Approach that allowed to approach the existing reality in the National Open University (UNA) in Venezuela, thus showing the fragmentation between the mathematical and didactic knowledge regarding the teaching function of the content specialist, the advisor, the medium-teacher or instructional module.